(untitled) (INNOVATIVE ECONOMY, 2025)
Zhyvko M.A. CIRCULAR CLUSTERS OF CHINA: BENCHMARKING IN THE CONTEXT OF GLOBAL ECONOMIC FRAGMENTATION Purpose. The aim of the article is to study the effectiveness of China’s circular clusters as an innovative model of economic development in the conditions of global economic fragmentation. Methodology of research. The methodological basis of the study is based on the use of general scientific methods that provide a comprehensive approach to the study of circular clusters in China and their role in the conditions of global economic fragmentation. In particular, the study used induction and deduction methods to collect, systematize and analyze data, which helped to identify trends and cause-and-effect relationships in the development of circular clusters. Analysis and synthesis were used to identify key trends in the formation of the circular economy, which allows us to determine the specifics of its impact on the sustainability and resource efficiency of industrial regions. The abstract and logical method helped to generalize information from various sources to create a holistic understanding of the problem and formulate theoretical conclusions. The comparative method allowed comparing Chinese circular clusters with similar structures in other countries, identifying the main areas of implementation of circular practices, and establishing their impact on economic self-sufficiency. The study used tabular and graphical methods to visualize statistical data in order to highlight the main trends and patterns of circular clusters development. Findings. It is established that China’s circular clusters have become an effective tool for increasing economic sustainability and environmental responsibility, especially in the context of global economic fragmentation. It is shown that China is investing in infrastructure that allows for closed production cycles, for example, leading clusters are implementing integrated waste collection and recycling systems that can significantly reduce the volume of industrial waste. It is considered that China’s experience is a valuable model for countries that want to minimize the environmental footprint of their industrial clusters and improve economic sustainability. It is proved that the development of circular clusters can be a powerful strategy for reducing the impact of economic fragmentation and strengthening the resilience of industrial systems, making them less dependent on external factors. Originality. It is established how circular clusters can reduce China’s dependence on imported resources, which is important in light of global constraints and market fragmentation. A methodology for assessing the environmental performance of circular clusters based on the analysis of resource conservation and reduction of industrial waste is developed, which provides new data for assessing the contribution of such clusters to sustainable development. A structured approach to benchmarking Chinese clusters is proposed, identifying which aspects of this experience can be adapted by other countries. The article reveals how Chinese circular clusters strengthen competitive advantages in global markets by optimizing costs and creating environmentally friendly products, which is especially valuable for export-oriented economies. Practical value. The proposed recommendations can be used to test China’s experience in developing circular clusters as an effective strategy for increasing economic and environmental sustainability in other countries. The results of the study may be useful for companies focused on international markets, as environmentally friendly technologies are becoming a significant factor in competitiveness. Key words: circular clusters, benchmarking, global fragmentation, sustainable development, economic disintegration, innovative models, global economy, cluster strategies, circular economy, economic transformation.